Multi Modal Oriented Learning Model in Science Subjects for Grade Four of Elementary School - Sari, Sintyan; Saputra, Setia Yunus; Kumalasani, Maharani Putri (Universitas Pendidikan Ganesha, 2025)
This research is motivated by the low involvement and learning outcomes of students in science subjects in grade 4 of Elementary School, which is caused by using conventional and less varied learning methods. This study aims to analyze the effectiveness of implementing multimodal-oriented PBL in learning to foster student collaboration and understanding of science concepts and to recognize the impact of PBL implementation on 21st-century development. This research used a descriptive qualitative method involving students and elementary school educators as research subjects. The data collection methods used were observation and interviews. The data analysis technique used qualitative descriptive analysis. The results of the study identified that the implementation of the multimodal-oriented problem-based learning model was efficient in producing imaginative science learning; the impact of this study helped educators to recommend innovative learning methods by PBL syntax with various modalities and provide practical assessments to be suggested as relevant and effective alternatives to improve the quality of learning. In conclusion, the application of multi-modal oriented learning models in science subjects can improve students' conceptual understanding and active involvement in the learning process, with the implication that teachers need to systematically integrate various learning modes such as visual, auditory, and kinesthetic to accommodate diverse learning styles in the classroom.